2015
DOI: 10.1001/jama.2015.8371
|View full text |Cite
|
Sign up to set email alerts
|

Violence in the United States

Abstract: IMPORTANCE-Interpersonal violence, which includes child abuse and neglect, youth violence, intimate partner violence, sexual violence, and elder abuse, affects millions of US residents each year. However, surveillance systems, programs, and policies to address violence often lack broad, cross-sector collaboration, and there is limited awareness of effective strategies to prevent violence.OBJECTIVES-To describe the burden of interpersonal violence in the United States, explore challenges to violence prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(122 citation statements)
references
References 65 publications
(86 reference statements)
4
100
0
6
Order By: Relevance
“…A North American study has shown that people experience different types of abuse, and the aggressor can also perpetrate abuses of different natures against the same person (18) . Physical violence, also considered one of the most prevalent in the literature (17) , is alarming due to some of its consequences, such as burns, fractures and bruises.…”
mentioning
confidence: 99%
“…A North American study has shown that people experience different types of abuse, and the aggressor can also perpetrate abuses of different natures against the same person (18) . Physical violence, also considered one of the most prevalent in the literature (17) , is alarming due to some of its consequences, such as burns, fractures and bruises.…”
mentioning
confidence: 99%
“…Documented individual risk factors include substance use, little education, low socio-economic status (SES) and poor mental health. [17][18][19] Relationship risk factors include family conflict and gang involvement. 20,21 Community risk factors include social disintegration (breakdown of norms that exist in a community), neighbourhood SES, and low community efficacy (the ability of a group to act collectively).…”
Section: Discussionmentioning
confidence: 99%
“…Forced and early marriage, sex trafficking, rape, female genital mutilation, and the exertion of power and control over contraceptive and pregnancy choices are all types of violence against women and girls [21,23]. Interpersonal violence, including sexual violence, is also a major public health problem in the United States [24]. Unwanted pregnancies and sexually transmitted infections are two possible consequences of sexual victimization.…”
Section: Sexual Violence and Family Planningmentioning
confidence: 99%
“…Unwanted pregnancies and sexually transmitted infections are two possible consequences of sexual victimization. Only a small percentage of violent incidents are reported to health care clinicians or law enforcement agencies [24] and sexual violence can also go undetected in mental health services [25]. Patients with major mental disorders are at an elevated risk of becoming victims of violence, including sexual violence [26,27].…”
Section: Sexual Violence and Family Planningmentioning
confidence: 99%